2017
DOI: 10.1016/j.jcmg.2016.03.022
|View full text |Cite
|
Sign up to set email alerts
|

CAC Score Improves Coronary and CV Risk Assessment Above Statin Indication by ESC and AHA/ACC Primary Prevention Guidelines

Abstract: Current ESC and AHA/ACC guidelines lead to markedly different recommendation regarding statin therapy in a German primary prevention cohort. Quantification of CAC score in addition to the guidelines improves stratification between subjects at high versus low risk for coronary events, indicating that CAC scoring may help to match intensified risk factor modification to atherosclerotic plaque burden as well as actual risk while avoiding therapy in subjects with low coronary atherosclerosis that have low 10-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(87 citation statements)
references
References 28 publications
3
82
0
2
Order By: Relevance
“…Coronary atherosclerosis is a major cause of coronary heart disease (CHD). The common risk factors contributing to the development of CHD are advanced age, smoking, obesity, hypertension, high cholesterol and diabetes, etc . In the case of coronary atherosclerosis, lipids drive inflammation on the endothelium and accelerate plaque formation on vulnerable coronaries .…”
Section: Introductionmentioning
confidence: 99%
“…Coronary atherosclerosis is a major cause of coronary heart disease (CHD). The common risk factors contributing to the development of CHD are advanced age, smoking, obesity, hypertension, high cholesterol and diabetes, etc . In the case of coronary atherosclerosis, lipids drive inflammation on the endothelium and accelerate plaque formation on vulnerable coronaries .…”
Section: Introductionmentioning
confidence: 99%
“…A similar analysis was recently preformed by Mahabadi et al [14], who applied both AHA/ACC guidelines and the ESC guidelines to participants of the Heinz Nixdorf Recall study. Similar to MESA, this study is a prospective cohort of individuals who did not have any known CVD at baseline.…”
Section: Use Of Cac In Light Of Recent Guidelines?mentioning
confidence: 91%
“…This study found that for both guidelines, and irrespective of statin indication, individuals with higher CAC scores had a higher CHD and CVD event rate (Fig. 6) [14]. Notably, CAC was absent in 43% of individuals who were met statin indications by the ESC guidelines and 53% of the individuals who met statin indication by the AHA/ACC guidelines.…”
Section: Use Of Cac In Light Of Recent Guidelines?mentioning
confidence: 98%
“…A CACS of zero (no detectable coronary calcium) has been said to provide a “warranty” against CV events for 10–15 years . For patients in whom statin therapy is recommended by traditional risk factor evaluation, a CACS of zero has been shown to have a very low event risk, on the order of 2–5 events per thousand patient years …”
Section: Coronary Artery Calcium Score and Ascvd Riskmentioning
confidence: 99%